ONOMASTICS AND FICTIONALIZED SPACE: AFFIRMATION OF IDENTITY IN THE WORK OF MOHA SOUAG - Lihi, Ali (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
In order to understand the resonance of identity in the work of Moha Souag, a Moroccan author of French expression, we aim in this article to demonstrate how onomastics, as a social and identity mark, constructs and shapes the identity of the characters. We study the identity dimension of onomastic as rising of a reflection on the fictionalized space where the author has put his characters. By doing that, we dwell on the way in which Moha Souag’s work functions and presents itself. This is to conclude that the identity in the said work is elaborated through the projection of the individuals’ attributes on the group and on the places. In short, the fictionalization of territory favors the control of the social space by offering the work a concrete and identifiable field.